Breaking walls: film narratives on Central american «irregular» migrations - Mendez Gomez, Delmar Ulises (2020)
Introduction It has been argued that documentary film is a medium that offers other narratives on the different social problems, beyond references by the hegemonic media. Objective For this reason, this article aims to analyze the narrative forms of irregular Central American migrations in documentary film. For this, we recovered two documentaries: What is the way home? (2009), by Rebecca Cammisa, and Casa en tierra ajena (2017), by Ivannia Villalobos and Carlos Sandoval, to identify and reflect on what is said about migration, how it is stated and presented to migrants, how the lived experience is related along the way and the causes of migration. Method Given the nature of the research, we recover the approaches of visual and film studies, which allow us to analyze the stories, scenes, characters and dialogues that make up the film account.       Results Among the results, it is worth highlighting that documentary film enables an emerging space to socialize and visualize the experiences of migrants on their journey to the United States and their passage through Mexico. Conclusions It is concluded that documentary film moves away from the discourses and media visions of the hegemonic media, to offer other views of mobility and enhance the visibility of the denied, which allows us to understand the causes that motivate Central American migration, which go further beyond the simple assertion that is given in search of «the american dream».